Measurements of Ultrasonic Wave Velocities in Ice Cores from Greenland and Antarctica. - Bennett,Hugh F. (1972)
Detailed ultrasonic velocity measurements were made on snow and ice cores from Greenland and Antarctica in order to study velocity anisotropy and its relationship to the petrofabric analysis of these cores. In addition, ultrasonic velocities were measured in the near-surface snow layers at Byrd Station and South Pole Station, Antarctica, to provide a detailed velocity profile in the region of the ice sheet where the velocity is greatly influenced by the snow structure. The experimental arrangement, including the design of equipment, measurement errors, techniques, and problems encountered in the study, is discussed. The theory of wave propagation in a general anisotropic medium is reviewed and a detailed presentation of this theory, concerning transversely isotropic media, is given. A method is developed for calculating a theoretical velocity model from the petrofabric analysis of the ice cores, thus providing a means of testing the theory with field and laboratory observations. (Author)